Water-energy-nutrient nexus: Multi-sectoral metabolism analysis and technical path optimization for eco-towns. (1st January 2021) - Wen, Zongguo; Xie, Yiling; Chen, Chen; Li, Yue; Xu, Patrick
Abstract: The multi-sectoral metabolisms of substance and energy in rural areas are complex, whose optimization is the key to realize resource recycling and energy cascade utilization. Through Substance Flow Analysis (SFA), we establish a Multi-sectoral Metabolism Analysis Model specific to rural areas (MMAM-rural), and investigated the multi-sectoral metabolisms of Liujiadian Town in Beijing city. We simulate the water, energy and nutrients (carbon, nitrogen and phosphorus) metabolisms of a total of five sectors (water, waste management, livestock husbandry, forestry, and residential sectors), and identify the key metabolic flows significant for improving regional metabolism performance of Liujiadian Town. For further technical path optimization, we construct an index system made up of resource utilization efficiency, environmental burden of production and recycling efficiency, and adopt Scenario Analysis to evaluate the water-energy-nutrient metabolism performance under multiple technical scenarios different from disposals of agricultural waste, livestock and poultry manure, and domestic waste. Results show that, for agricultural wastes disposal, the combination scenario of edible fungi cultivation, anaerobic fermentation and aerobic composting is optimal. For livestock and poultry manure, all pig manure should be composted after anaerobic fermentation. For domestic wastes, food wastes require anaerobic fermentation and composting for optimization. Our study provides a model to evaluate metabolism performance of water-energy-nutrient nexus in rural areas, and raises solutions for optimization in the process of eco-town construction. Highlights: Multi-sectoral metabolism of water-energy-nutrient nexus of a case in rural Beijing was analyzed. Metabolism performance index was established to evaluate technical scenarios synthetically for optimization. Combination of edible fungi cultivation, anaerobic fermentation and composting is optimal for agricultural waste disposal. Provide technical suggestions for eco-town construction through technical path optimization.